(untitled) (Journal of Partial Differential Equations, 2003)
Let 03a3_1 and 03a3_2 be m and n dimensional Riemannian manifolds of constant curvature respectively. We assume that w is a unit constant m-form in 03a3_1 with respect to which 03a3_0 is a graph. We set v = 2329e_1 2227 2026 2227 e_m, 232a), where e_1, 2026, e_m is a normal frame on 03a3_t. Suppose that 03a3_0 has bounded curvature. If v(x, 0) 2265 v0 > frac sqrtp 2 for all x, then the mean curvature flow has a global solution F under some suitable conditions on the curvatrue of 03a3_1 and 03a3_2."